Effective dosage of growth differentiation factor‐9β in folliculogenesis and angiogenesis in the sheep ovarian tissues grafted onto chick embryo chorioallantoic membrane. Issue 8 (4th June 2020) - Vatanparast, Mahboubeh; Moshrefi, Mojgan; Yari, Nahid; Khalili, Mohammad Ali; Macchiarelli, Guido; Palmerini, Maria Grazia
Abstract: Aim: Scientists have tried to culture and transplant the ovarian tissues (OT), to preserve fertility in cancer patients. However, one of the main limitations to the applicability of this technique is the folliculogenesis disruption after transplantation. Due to the roles exerted by growth differentiation factor‐9β (GDF9β), we decided to determine the most effective dose of GDF9β on promotion of folliculogenesis and angiogenesis in sheep OT grafted onto the chick chorioallantoic membrane (CAM). Methods: Fresh sheep OT were grafted onto the CAM for 5 days, and divided into four groups based on the addition of increasing doses of GDF9β (0, 150, 200 and 250 ng/mL). Following culture, histological (hematoxylin and eosin [H&E] staining) and immunohistological studies (Ki‐67) were done. Fibrotic and necrotic regions were measured using MICROVISIBLE software. For comparing the follicle development rates between the groups as well as differences in the Ki‐67‐positive follicles, analysis of variance was applied. Results: In both 200 and 250 ng/mL GDF9β groups, significantly higher rates of intermediary and primary follicles were observed, also the numbers of good quality follicles increased in the aforementioned groups and the rates of fibrotic and necrotic areas decreased. Moreover, in the 200 and 250 ng/mL GDF9β groups, the number of capillaries and the proliferative activity increased. The lower dose of GDF9β (150 ng/mL) neither activated the primordial follicles nor lead to an increase in the number of growing follicles. Conclusion: Addition of high dosages of GDF9β to the OT, grafted onto the CAM resulted in higher folliculogenesis and better transplantation features due to improvement in angiogenesis.